2016
DOI: 10.1248/bpb.b16-00332
|View full text |Cite
|
Sign up to set email alerts
|

Epalrestat Upregulates Heme Oxygenase-1, Superoxide Dismutase, and Catalase in Cells of the Nervous System

Abstract: Heme oxygenase (HO)-1 has potent antioxidant and anti-inflammatory functions. Recent studies have shown that the upregulation of HO-1 is beneficial to counteract neuroinflammation, making HO-1 a new therapeutic target for neurological diseases. We have reported that epalrestat (EPS), which is currently used for the treatment of diabetic neuropathy, increases HO-1 levels through the activation of nuclear factor erythroid 2-related factor 2 (Nrf2) in bovine aortic endothelial cells. In this study, we tested the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
20
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 23 publications
(26 citation statements)
references
References 45 publications
6
20
0
Order By: Relevance
“…HO‐1 expressed at sites of rat sciatic nerve injury in the peripheral nervous system may contribute to cellular adaptive function when cells have lost contact with axons, and appears to play a crucial role in nerve regeneration . Upregulation of HO‐1 in Schwann cells may also enhance neuroprotection . Here, bFGF stimulated HO‐1 expression in sciatic nerve cells, as was previously reported in spinal astrocyte culture .…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…HO‐1 expressed at sites of rat sciatic nerve injury in the peripheral nervous system may contribute to cellular adaptive function when cells have lost contact with axons, and appears to play a crucial role in nerve regeneration . Upregulation of HO‐1 in Schwann cells may also enhance neuroprotection . Here, bFGF stimulated HO‐1 expression in sciatic nerve cells, as was previously reported in spinal astrocyte culture .…”
Section: Discussionsupporting
confidence: 80%
“…39 Upregulation of HO-1 in Schwann cells may also enhance neuroprotection. 40 Here, bFGF stimulated HO-1 expression in sciatic nerve cells, as was previously reported in spinal astrocyte culture. 31 We also demonstrated that vein wrapping further stimulated HO-1 expression in sciatic nerve tissue.…”
supporting
confidence: 81%
“…Consistent with previous studies on the effects of vein wrapping, we found that bFGF/CS stimulates Hmox1 mRNA and HO‐1 protein expression, while PBS/CS does not. Previous studies have shown that HO‐1 induction results in anti‐nociceptive effects and alleviation of neuropathic pain . Our results suggest that bFGF/CS‐mediated HO‐1 expression may contribute to pain relief.…”
Section: Discussionsupporting
confidence: 58%
“…According to the previous findings, heme oxygenase (HO)-1 has potent antioxidant and anti-inflammatory functions; however, EPS upregulates HO-1, dismutase, and catalase by activating Nrf2 and suggests that EPS has the beneficial effect on improvement of several neurological disorders [12].…”
Section: Discussionmentioning
confidence: 97%
“…It is reported for anti-inflammatory and antioxidant effects using rat Schwann cell and human neuroblastoma cell line [12][13][14]. Therefore, the antiinflammatory and anti-oxidant properties of EPS can be beneficial in the management of neurodegenerative disease by improving the memory and learning in an animal model.…”
Section: Introductionmentioning
confidence: 99%